Alcohol harm reduction advertisements: A content analysis of topic, objective, emotional tone, execution and target audience - Dunstone, K.; Brennan, E.; Slater, M.; Dixon, H.; Durkin, S.; Pettigrew, Simone; Wakefield, M. (BioMed Central Ltd, 2017)
© 2017 The Author(s). Background: Public health mass media campaigns may contribute to reducing the health and social burden attributed to alcohol consumption, but little is known about which advertising characteristics have been used, or have been effective, in alcohol harm reduction campaigns to date. As a first step towards encouraging further research to identify the impact of various advertising characteristics, this study aimed to systematically identify and examine the content of alcohol harm reduction advertisements (ads). Method: Ads were identified through an exhaustive internet search of Google, YouTube, Vimeo, and relevant government and health agency websites. Eligible ads were: English language, produced between 2006 and 2014, not primarily focused on drink-driving or alcohol in pregnancy, and not alcohol industry funded. Systematic content analysis of all ads was performed; each ad was double-coded. Results: In total, 110 individual ads from 72 different alcohol harm reduction campaigns were identified, with the main source countries being Australia (40%) and the United Kingdom (26%). The dominant topic for 52% of ads was short-term harms, while 10% addressed long-term harms, 18% addressed underage drinking, 17% communicated a how-to-change message, and 3% advocated for policy change. The behavioural objective of most ads was to motivate audiences to reduce their alcohol consumption (38%) or to behave responsibly and/or not get drunk when drinking (33%). Only 10% of all ads mentioned low-risk drinking guidelines. Eighty-seven percent of ads used a dramatisation execution style and 74% had a negative emotional tone. Ninety percent of ads contained messages or content that appeared to target adults, and 36% specifically targeted young adults. Conclusions: Some message attributes have been employed more frequently than others, suggesting several promising avenues for future audience or population-based research to compare the relative effectiveness of different characteristics of alcohol harm reduction ads. Given most alcohol-attributable harm is due to long-term disease, these findings suggest future campaigns may fill a potentially important gap if they were to focus on long-term harms. There is scope for such long-term harm campaigns to place greater emphasis on encouraging reduced personal consumption of alcohol, potentially through more frequent communication of low-risk drinking guidelines.